Carcinoembryonic antigen‐specific, fluorescent image‐guided cytoreductive surgery with hyperthermic intraperitoneal chemotherapy for metastatic colorectal cancer. Issue 4 (21st January 2020) - Schaap, D. P.; de Valk, K. S.; Deken, M. M.; Meijer, R. P. J.; Burggraaf, J.; Vahrmeijer, A. L.; Kusters, M.; ,
Abstract : This multicentre pilot study investigated the role of peroperative carcinoembryonic antigen (CEA)‐specific fluorescence imaging during cytoreductive surgery–hyperthermic intraperitoneal chemotherapy surgery in peritoneal metastasized colorectal cancer. A correct change in peritoneal carcinomatosis index (PCI) owing to fluorescence imaging was seen in four of the 14 included patients. The use of SGM‐101 in patients with peritoneally metastasized colorectal carcinoma is feasible, and allows intraoperative detection of tumour deposits and alteration of the PCI. Augmented reality guidance